2022
DOI: 10.1007/s10826-022-02348-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Family Environment and Adolescent Delinquent Behaviours in China

Abstract: Please refer to any applicable terms of use of the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…On the other hand, peer pressure and economic factors such as poverty can contribute to the development of delinquent behavior. Finally, the family environment, which includes structure, parental behaviors, attachment patterns, and economic conditions, is critical in shaping the emergence of delinquent behaviors [1,2].…”
Section: Family Environmentmentioning
confidence: 99%
“…On the other hand, peer pressure and economic factors such as poverty can contribute to the development of delinquent behavior. Finally, the family environment, which includes structure, parental behaviors, attachment patterns, and economic conditions, is critical in shaping the emergence of delinquent behaviors [1,2].…”
Section: Family Environmentmentioning
confidence: 99%
“…Since, Yue did a lot of research in China based on the EMBU scale and adapted the EMBU scale to the actual situation in China, many Chinese scholars have also adopted their modified scales, and all of these studies have confirmed that their scales have good reliability and validity [32]. Though favoritism has been identified to be culture-specific, cross-cultural stability of the EMBU based on data from Chinese subjects is satisfactory [33,34]. Cronbach's alpha for the EMBU in the current study was 0.94.…”
Section: Perceived Parenting Stylesmentioning
confidence: 99%